Efeito da adição de ferro e ácido nas características da qualidade do bolo - Campêlo, Wilma Félix (2004)
Epidemiological and clinical studies have shown that the needs of certain nutrients are not fulfilled by alimentation. Therefore, it is very important that the basic daily aliments be enriched in order to compensate the nutritional loss occurred in the industrialization process. Hence, this study aims to analyze the effect of the enrichment of two types (ferrous sulphate - FS and Ferrochel® amino acid chelate - FQ) and three levels (30, 40, and 50% of Dietary Reference Intakes - DRI) of iron and folic acid in the characteristics of the cake quality. Every 100g of buckwheat flour was enriched with 4.8, 6.4, and 8.0 mg of iron, which is equivalent to 30, 40, and 50% of the DRI, respectively, and with 150μg of folic acid. Sensorial, physical, physical-chemical and chemical analyses were conducted in the cakes made with the enriched flour. The enriched cakes did not present statistical difference in the following sensorial parameters: overall appearance, smoothness, and sweetness. In the parameter crust color, the cake control presented mean of satisfaction statistically higher than that of FQ 50% enriched cake only. In the analysis of texture, difference in the means was found only in the 40% enriched cakes, where the FQ enriched cake presented a mean higher than that of the FS enriched cake. The mean intensity of the crust color was higher in the control cake than in the FS 30% and FQ 40% enriched cakes. Statistical differences in the intensity of the color of the crumb were found in the 40% enriched cakes only, where the mean of the FS cakes was higher than that of the FQ cakes. In the physical, physic-chemical and chemical, analyses, no differences were found in the analyses of proteins and pH. Humidity and lipids were different between the cake control and flour (type of iron)/enrichment combinations and among the enrichments. Differences in the ash and in the carbohydrates were found between the cake control and flour/enrichment combinations, and the iron presented difference among the flours, among the enrichments, in the interaction flour x enrichment and the cake control with the flour/enrichment combinations. It was concluded that the enrichment of the cakes with iron sulfate and iron amino acid chelates of 30, 40, and 50% of the IDR kept acceptable the level of sensorial quality stated by the consumers, and therefore can be a feasible technological alternative of aliments enriching